Study on chemical constituents from Ixeris dentata - Le Thi Huyen; Nguyen Tien Dung (Vietnam Journal of Science and Technology, 2023)
Ixeris dentata (Thunb. ex Thunb.) Nakai (family Asteraceae) a plant widely distributed in Viet Nam, is a perennial herb that grows to a height of 0.5 m. It has been used as a medicinal herb medicine since ancient times for the treatment of calculi, dyspepsia, indigestion, pneumonia, hepatitis, contusion, and tumors in Northeast Asia. The biological activities of this plant have been shown to be neuroprotective, anti-mutagenic, anti-hyperlipidemic, anti-inflammatory, anti-allergic, and anti-proliferative activities. It is also composed of aliphatics, triterpenoids, sesquiterpene, and glycosides. However, research on the phytochemistry of this plant has yet to be conducted in Viet Nam. In this study, five phenolics including chlorogenic acid (1), 3,5-di-O-caffeoylquinic acid (2), 4,5-di-O-caffeoylquinic acid (3), citrusin C (4), 4-allyl-2,6-dimethoxyphenol O-β-D-glupyranoside (5), and two sesquiterpene lactones, 8-epidesacylcynaropicrin glucoside (6) and ixerisoside A (7) were isolated from the methanol extract of the leaves of Ixeris dentata using combined chromatographic methods. Their chemical structures were determined by analysis of MS, NMR spectra data as well as comparison with those reported in the literature.